Effect of thermocycling on hardness, absorption, solubility and colour change of soft liners - Mancuso, Daniela Nardi [UNESP]; Goiato, Marcelo Coelho [UNESP]; Rossatti Zuccolotti, Bruna Carolina [UNESP]; Moreno, Amalia [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Wiley-Blackwell, 2012)
Objective: The effect of artificial ageing on the hardness, absorption, solubility, and colour of soft denture liners was investigated.Materials and methods: Liner materials based on acrylic resin (Trusoft) or silicone (Dentusil, Ufi Gel P, and Ufi Gel SC) were tested before and after 2000 thermal cycles. A total of 20 specimens of each material were tested. Half of the specimens were used for hardness and colour evaluation, and the remainder for absorption and solubility tests. The hardness evaluation was carried out using a Shore A durometer, while absorption and solubility tests were performed by storing samples in a desiccator and weighing daily until reaching constant mass (W1). After thermocycling, the samples were again weighed (W2) and dried (W3). Colour was measured using a spectrophotometer. Statistical analysis was performed using GraphPad InStat at the p < 0.05 level.Results: Thermocycling significantly affected the hardness of the specimens. The Trusoft material exhibited the highest absorption (1.48 +/- 0.48), solubility (1.26 +/- 0.28), and colour change (3.92 +/- 0.33), significantly different from the other materials. There were no significant differences among the silicones in terms of absorption, solubility, and colour change, except for the colour of Dentusil, which changed (0.83 +/- 0.11).Conclusion: It can be concluded that silicone liners performed significantly better compared to acrylic resin.
Keywords: hardness; colour; absorption; solubility; silicone